Association among physical, psychiatric and socioeconomic conditions and WHOQOL-Bref scores - Sergio Luís Blay; Marina Sthal Merlin Marchesoni (Cadernos de Saúde Pública, 2011)
The aim of this study is to investigate the impact of psychiatric morbidity, depression, cognitive deficit, number of self-reported illnesses and socio-demographic variables on the WHOQOL-Bref domain scores. WHOQOL-Bref domain scores are substantially affected by psychiatric morbidity and income. Depression, the number of self-reported illnesses and the female gender also explain the variability of other domains to a lesser extent.